2001
DOI: 10.1542/peds.107.1.e7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Use of Television During Meals and Children's Food Consumption Patterns

Abstract: ABSTRACT. Objective. We examined relationships between the presence of television during meals and children's food consumption patterns to test whether children's overall food consumption patterns, including foods not normally advertised, vary systematically with the extent to which television is part of normal mealtime routines.Methods. Ninety-one parent-child pairs from suburbs adjacent to Washington, DC, recruited via advertisements and word of mouth, participated. Children were in the fourth, fifth, or six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
267
2
37

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(334 citation statements)
references
References 45 publications
18
267
2
37
Order By: Relevance
“…5,41 Research has also shown differential eating patterns between those who eat in front of the TV and those who do not. 12 Other potential mediating variables could include increased exposure to food-related advertising directed at children, 42,43 or interference with sleep. Two studies have demonstrated that children who receive less than 10 h of sleep per night were more likely to be obese, 44,45 and additional research has shown that having a TV in the bedroom is associated with fewer hours of sleep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,41 Research has also shown differential eating patterns between those who eat in front of the TV and those who do not. 12 Other potential mediating variables could include increased exposure to food-related advertising directed at children, 42,43 or interference with sleep. Two studies have demonstrated that children who receive less than 10 h of sleep per night were more likely to be obese, 44,45 and additional research has shown that having a TV in the bedroom is associated with fewer hours of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…2 Averaging at least 3 h a day, child media exposure to TV exceeds other media, including exposure to videos/DVDs/movies, print media, audio media, computers and video games. 2 High amounts of TV use have been associated with many negative outcomes, including poor scholastic performance, 7,8 sleep deprivation, 9,10 child requests for advertised foods, 11 eating fewer fruits and vegetables and more pizza/snack food/soda, 12 greater consumption of high-fat foods 13 and higher BMI. [4][5][6]14 Overweight is associated with many diseases, 1,[15][16][17] and the greater the degree of overweight as a child, the greater the likelihood that child will be overweight as an adult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] These findings may be associated with decreased energy expenditure and the increased energy intake either from overeating due to a delay in normal mealtime satiation 11 or snacking that occurs during inactive times such as TV viewing. [12][13][14][15] In addition, children may be more likely to choose unhealthy foods as a result of exposure to TV food commercials. 16 Reducing screen-related sedentary behaviour (S-RSB) is essential to prevent and treat childhood obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. (Videon & Manning, 2003) and by consumption of foods high in fat and sugar (Coon, Goldberg, Rogers, & Tucker, 2001). In addition, several cross-sectional studies have suggested that the frequency of family meals is positively associated with consumption of healthier foods (e.g., Neumark-Sztainer, Hannan, Story, Croll, & Perry, 2003).…”
mentioning
confidence: 99%